Índices zootécnicos, reprodutivos e parâmetros bioquímicos de fêmeas de jundiá Rhamdia quelen alimentadas com diferentes níveis de proteína e lipídio - Coldebella, Ivanir José (2010)
In this study were evaluated the zootechnics, reproductive aspects and biochemical s parameters aspects of female catfishes fed with three lipids and proteins levels on diets. Two experiments were conducted, the first being held between July 15th and October 15th, 2008, followed by a period of 14 days to create the post-larvae. We used 66 females with 14 months old (weight between 465,1 and 690,3g). 18 females were slaughtered for evaluation of biochemical s and histological parameters and 54 were distributed on six 1m³-net cage, fed at 9 a.m. and 4 p.m., at ease, during 90 days, with pelletized rations containing 28, 34 and 40% of PB and 14% of total lipids. Twelve females were induced to spawn to reproductive evaluation (fertilization rate, egg s number, eggs and larvae s biometrics and prost-larvae s growth). At experiment I, the results indicated that the increase of protein s level at diet didn t influence the zootechnics, reproductive and biochemical s parameters, however the 28% of PB level was superior for the post-larvae s growth on the variables weight, length and weight versus survival in 14 days. The second experiment was performed between July 15th and October 15th, 2009, and we used the best diet of first experiment (28% of PB and 14% of lipids), settling the 8, 14 and 20% of lipids and 28% of PB levels. In this experiment was selected 93 females with 14 months old and weighting between 596,28 and 640,4g and 66 of which was distributed on six net cages and 27 was slaughtered for evaluation of biochemical s and histological parameters and the gonad's lipid profile. For both experiments were followed the same procedure, just adding, at the second, the evaluation of ovaries and muscles lipids profile. The results of experiment II also didn t show difference to the zootechnics and biochemical s parameters, but there was a linear increase in visceral fat index with the increased level of lipid in the diets. The fatty acids profile didn t differ between the treatments, but there was variation in concentration. The egg s diameter and area were significantly smaller to the 20% of lipids level, damaging the post-larvae s growth, survival and weight versus survival. The best reproductive s answers to catfishe s females were obtained with diets containing 28% of PB and between 8 and 14% of total lipids.